2021
DOI: 10.3390/biomedicines9121920
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review with Meta-Analysis: Diagnostic Accuracy of Pro-C3 for Hepatic Fibrosis in Patients with Non-Alcoholic Fatty Liver Disease

Abstract: The prevalence and severity of non-alcoholic fatty liver disease (NAFLD) is increasing, yet adequately validated tests for care paths are limited and non-invasive markers of disease progression are urgently needed. The aim of this work was to summarize the performance of Pro-C3, a biomarker of active fibrogenesis, in detecting significant fibrosis (F ≥ 2), advanced fibrosis (F ≥ 3), cirrhosis (F4) and non-alcoholic steatohepatitis (NASH) in patients with NAFLD. A sensitive search of five databases was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
(81 reference statements)
0
27
0
Order By: Relevance
“…A recent series of authoritative systematic reviews and meta-analyses conducted by members of the EU IMI2-funded LITMUS consortium 26 have collated published evidence on performance in NAFLD for a range of fibrosis biomarkers. [27][28][29][30][31][32] In general, non-invasive biomarkers are highly effective at ruling out the presence of advanced fibrosis or cirrhosis, exhibiting negative predictive values (NPVs) >90% in many cases; however, their positive predictive values (PPVs) are often more modest, and they are unable to accurately discriminate individual fibrosis stages. Both positive and negative predictive values are heavily influenced by the prevalence of the target condition in the population to which the biomarker is applied.…”
Section: Diagnosis and Staging Of Liver Fibrosis In Chronic Liver Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent series of authoritative systematic reviews and meta-analyses conducted by members of the EU IMI2-funded LITMUS consortium 26 have collated published evidence on performance in NAFLD for a range of fibrosis biomarkers. [27][28][29][30][31][32] In general, non-invasive biomarkers are highly effective at ruling out the presence of advanced fibrosis or cirrhosis, exhibiting negative predictive values (NPVs) >90% in many cases; however, their positive predictive values (PPVs) are often more modest, and they are unable to accurately discriminate individual fibrosis stages. Both positive and negative predictive values are heavily influenced by the prevalence of the target condition in the population to which the biomarker is applied.…”
Section: Diagnosis and Staging Of Liver Fibrosis In Chronic Liver Dis...mentioning
confidence: 99%
“…Fewer large cohort studies are available to assess the performance of PRO-C3; however, a recent meta-analysis of 2,058 patients with NAFLD in 35 studies reported that PRO-C3 alone could detect advanced fibrosis with an AUROC of 0.79 (0.73-0.82). 27 Both ADAPT and FIBC3 have also been shown to outperform FIB-4 and PRO-C3 alone. 57 Published head-to-head comparisons of proprietary biomarkers are lacking although conference reports suggest that, at best, the currently available direct biomarkers only marginally outperform FIB-4 when targeting the presence of advanced fibrosis.…”
Section: Diagnosis and Staging Of Liver Fibrosis In Chronic Liver Dis...mentioning
confidence: 99%
“…Results of FibroScan and ELF are indicative of the amount of liver fibrosis while those of PRO-C3 are also indicative of fibrogenesis, the process of active fibrosis synthesis. All three have been studied across multiple liver diseases, including NAFLD [ 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most of these tests use regular clinical parameters, except the ELF test. [137][138][139][140][141][142][143][144][145][146][147][148] 3.2 | Imaging modalities for the detection and evaluation of NAFLD/NASH Conventional ultrasound imaging (USA) is frequently used to establish liver steatosis. This technique has been included in the guidelines 149 and is widely available at relatively low cost.…”
Section: Noninvasive Liver Tests (Nilts)mentioning
confidence: 99%